Pengaruh Pembelajaran Ekonomi, Literasi Ekologi, dan Program Sekolah Adiwiyata terhadap Perilaku Konsumsi Ramah Lingkungan Siswa SMA Negeri 1 Ajibarang - Samini; Sambodo, Herman; Khotimah, Sofiatul (Jurnal Pendidikan Ekonomi Undiksha, 2022)
The understanding of economic learning by students has not been fully implemented in everyday life; the understanding of students of SMA Negeri 1 Ajibarang regarding ecological literacy is still low; the implementation of the Adiwiyata school program has not been maximized in seeking environmentally friendly consumption behavior for students. This research is a quantitative research conducted on students of SMA Negeri 1 Ajibarang class X, XII IPS and XII IPS with the aim of analyzing the influence of economic learning, ecological literacy, and adiwiyata school programs on the environmentally friendly consumption behavior of SMA Negeri 1 Ajibarang students. The population in this study was students of classes X, XI social studies and XII social studies at SMA Negeri 1 Ajibarang, with a total of 612 students. The samples used were taken from 86 respondents using accidental sampling techniques. The results of the research and data analysis obtained show that first, economic learning has a positive effect on students' environmentally friendly consumption behavior; second, ecological literacy positively affects students' environmentally friendly consumption behavior; and third, the adiwiyata school program does not have a positive effect on students' environmentally friendly consumption behavior.